Impact of extreme seasonal drought on ecosystem carbon‒water coupling across China - Meng-Tian Huang; Pan-Mao Zhai (Advances in Climate Change Research)
Water use efficiency (WUE) is a critical evaluation indicator of ecosystem responses to climate change and its extremes. However, the influence of the timing of extreme drought on the variation of ecosystem WUE under severe water stress has not been studied extensively. In particular, the modulation of drought impacts on WUE under regional hydro-climatic conditions and biome types is poorly understood. Considering observation-based ecosystem flux and drought index datasets, this study examined the impact of extreme seasonal drought on WUE in China and attempted to reveal the underlying drivers of seasonal variations in drought impacts. Results showed that the direction and magnitude of drought impacts on WUE depend on the occurrence time of extreme drought and the seasonal dynamics of regional ecological and climatic conditions. Across the vegetated regions in China, the most widespread reduction in WUE under extreme drought conditions was observed in summer, whereas approximately 60% of the study area showed positive changes in WUE under extreme drought conditions in spring. Furthermore, the co-regulation of drought characteristics and background environmental conditions in determining the impacts of extreme seasonal drought on ecosystem WUE is highlighted. Classification and regression tree analysis results illustrate that leaf area index (LAI) and drought timing dominated ecosystem WUE variation in response to extreme drought in China. Regions with lower LAI experienced more serious reductions in WUE under extreme drought. These findings indicate the importance of accounting for the interaction between drought seasonality and biome features in assessing drought impacts, thus contributing to improving the modelling of terrestrial ecosystem responses to climate extremes under global warming.